Media Sosial Dalam Perspektif Jurnalis Kampus - Agam, Muhammad Fuad; Rosyidin, Imron; Darsono, Dono (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2021)
This study has three research objectives, the first is to determine the extent of understanding of campus journalists in finding sources of inspiration for their coverage. The purpose of the second study was to determine the process of collecting campus journalists' news. The purpose of the third study was to determine the satisfaction of campus journalists in viewing information from the people's minds Instagram account. This study uses a descriptive content analysis method with a qualitative approach. Based on the research focus, the results of this study produced three results that interviewed every informant. The results of the first study understand the sources of inspiration for coverage seen from the captions, infographics, tracking issues and credibility. The results of the second study collect information data seen from the latest issues and the actuality of people's minds on Instagram. The results of the third research are satisfaction in the search for coverage, seen from the relevance of the news then the infographic which is very interesting to look at